Analisis Strategi Membangun Brand Awareness E- Commerce Shopee di Media Sosial dalam Meningkatkan Penjualan - Shevany, Machella (Jurnal Manajemen dan Inovasi (MANOVA), 2018)
The increasingly rapid development of e-commerce makes the competition even more stringent. Businesses are also required to compete competitively to retain consumers, one of which is by building brand awareness in the minds of consumers. Companies that have strong brands are certainly easily recognized by the public and can survive amid intense competition. For this reason, shopees need to implement effective strategies to build brand awareness. In building its brand awareness, shopee not only does marketing through its platform but also applies marketing strategies through social media that are useful as a means to further expand market reach. This research uses descriptive qualitative by literature study sourced from books, journals, and related web to research topics. The conclusion is that the strategy to build brand awareness in social media is very effective because it is easy to access and many people use social media in their activities. The use of effective shopee marketing strategies through social media makes it able to shift its competitors and reach the top position of brand awareness in Indonesia. The increase in brand awareness has made shopees more widely known and the sales have increased.